(3GdHGgs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3Efg hEf cGfJ GdcJH GdeDdaI aj JZRjQ GdHGg cKjQI ehLhOI, aEfj de CQ efgG Edi gPg GdZGjI cJGHkG cGajkG s
(3BNQgG (B:s
(3EdG CfG aj hbJfG gPG eTZhdhf, hEf fMf hLOfG aQGZkG aYdjfG Cf faYd Pdc Ef TGA Gddg s
(3Vef eLehY s
(3GfXQ CjkVG Qbe (B34"(3cJGH ai GdHGg (B"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B35 s
(3eUOQ GbJfGA GdCUd (B:s
(3HGJGajG (B- (3ghdGfOG (B(585 OR) s
Keywords: (3GdWHs